The Effectiveness Of Employing Interactive Video In Teaching Social And National Education In Developing Students' Communication Skills - Hassan, Salsabil (Eximia, 2023)
The study aimed to reveal the effectiveness of employing interactive video in teaching social and national education in developing communication skills among students. The study sample was distributed into two groups: an experimental group (25) students and a control group (23) students. The results showed that there were statistically significant differences in communication skills, and that the difference was in favor of the experimental group who were exposed to the interactive digital video teaching method compared to the group members. In light of this, the study presented a set of recommendations, most notably the necessity of using interactive video in teaching and enhancing it with pictures, video clips and effects that develop communication skills among students. The Internet, projectors and more.